Behavioral phenotyping of minipigs transgenic for the Huntington gene - Schramke, Sarah; Schuldenzucker, Verena; Schubert, Robin; Frank, Frauke; Wirsig, Maike; Ott, Stefanie; Motlik, Jan; Fels, Michaela; Kemper, Nicole; Hölzner, Eva; Reilmann, Ralf (Journal of neuroscience methods, 2016)
BACKGROUND: While several novel therapeutic approaches for HD are in development, resources to conduct clinical trials are limited. Large animal models have been proposed to improve assessment of safety, tolerability and especially to increase translational reliability of efficacy signals obtained in preclinical studies. They may thus help to select candidates for translation to human studies. We here introduce a battery of novel tests designed to assess the motor, cognitive and behavioral phenotype of a transgenic (tg) HD minipig model. NEW METHODS: A group of tgHD and wildtype (wt) Libechov minipigs (n=36) was available for assessment with (1) a gait test using the GAITRite(®) automated acquisition system, (2) a hurdle-test, (3) a tongue coordination test, (4) a color discrimination test, (5) a startbox back and forth test and (6) a dominance test. Performance of all tests and definition of measures obtained is presented. RESULTS: Minipigs were able to learn performance of all tests. All tests were safe, well tolerated and feasible. Exploratory between group comparisons showed no differences between groups of tgHD and wt minipigs assessed, but low variability within and between groups. COMPARISON WITH EXISTING METHOD(S): So far there are no established or validated assessments to test minipigs in the domains described. CONCLUSIONS: The data shows that the tests presented are safe, well tolerated and all measures defined can be assessed. Prospective longitudinal application of these tests is warranted to determine their test-retest reliability, sensitivity and validity in assessing motor, cognitive and behavioral features of tg and wt minipigs.
Keywords: učení; prasata; Behavior, Animal; Swine; vidění barevné; modely nemocí na zvířatech; Minipig; Discrimination, Psychological; fenotyp; Phenotype; jazyk; protein huntingtin; Equipment Design; Phenotyping; Color Vision; Huntingtonova nemoc; Huntingtin Protein; diskriminace (psychologie); chůze (způsob); Swine, Miniature; Huntington Disease; design vybavení; Neuropsychological Tests; Preclinical research; Animals, Genetically Modified; Gait; Animals; Learning; lidé; ženské pohlaví; Feasibility Studies; Humans; zvířata; pohybová aktivita; Disease Models, Animal; Motor Activity; Cognitive; chování zvířat; neuropsychologické testy; Animal models; Female; geneticky modifikovaná zvířata; Behavioral; studie proveditelnosti; Tongue; Motor; miniaturní prasata